An Early Cretaceous, medium-sized carcharodontosaurid theropod (Dinosauria, Saurischia) from the Mulichinco Formation (upper Valanginian), Neuquén Province, Patagonia, Argentina - Coria, Rodolfo Anibal (2019)
A new carcharodontosaurid taxon, Lajasvenator ascheriae gen. et sp. nov. is described. The new taxon is based on two specimens: MLL-PV-Pv-005 is a partial skeleton represented by a portion of the snout, partially articulated presacral vertebral series, four articulated caudal vertebra and fragments of the pelvic girdle; MLL-PV-Pv-007 includes the anterior ends of both dentaries, a quadratojugal, and fragments of cervical vertebrae, ribs and a possible tarsal bone. Lajasvenator is unique in having anterior projections on cervical prezygapophyses, lip-like crests on the lateral surfaces of cervical postzygapophyses, and bilobed anterior processes on cervical ribs. Lajasvenator material was collected from the terrestrial sandstones of the Valanginian Mulichinco Formation. It is the oldest carcharodontosaurid record from South America. This medium sized theropod was found associated with remains of the dicraeosaurid sauropod Pilmatueia, indeterminate diplodocid remains, and a yet unidentified iguanodontian-like ornithopod.